Rekonstruksi Regulasi Sebagai Optimalisasi Perlindungan dan Penegakan Hak Asasi Manusia dalam Sistem Ketatanegaraan Indonesia - Sun Fatayati; Ahmad Gelora Mahardika (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
Indonesia is a country based on law and has diverse citizens, so there are majorities and minorities; this makes Indonesia have many problems regarding human rights. a large number of cases of human rights violations that have occurred in Indonesia are due to a lack of understanding of human rights about the essential values that everyone owns so that people easily violate the rights of others, as well as protection and law enforcement that is not optimal in handling rights cases human rights. it is not only the minorities who must get protection, but the majority also really need to voice their rights as citizens of Indonesia. So that the lack of law enforcement and protection of human rights becomes a problem in solving problems related to human rights. Law enforcement related to human rights should be able to resolve human rights problems that occur in Indonesia. This paper was written by discussing how to optimize law enforcement in resolving cases related to human rights. so that problems related to human rights in Indonesia get solutions and optimal protection.